Species Diversity in Soil Seed Banks of Tropical Dry Deciduous Forests - Khare, Pratima; Khare, P. K. (Indian Forester, 2012)
Species diversity and density of buried seed bank in top 10cm. (0-5 cm and 5-10cm) of soil were studied in two tropical dry deciduous forests in Central India. Two sites namely, Mainpani and Ramna were selected for present study. Samples were collected 0-5 cm and 5-10 cm in three seasons, viz. postmonsoon, winter and summer. Seeds of total 34 species were recovered from soil samples belonging to 17 species of trees, 4 of shrubs and 13 of herbs. Result showed that highest density in upper layer (0-5 cm) was that of Anogeissus pendula (800 m-2 ) under inter canopy area in winter season at Mainpani. Maximum densities in case of shrub and herb species was found to have been contributed by Lantana camara (175 m-2 ) under canopy and Cassia tora (850 m-2 ) under inter canopy during summer and winter sampling at Ramna.